Techno-economic and uncertainty analysis of biomass to liquid (BTL) systems for transport fuel production - Dimitriou, Ioanna; Goldingay, Harry; Bridgwater, Anthony V. (Elsevier, 2018)
This work examines the technical and economic feasibility of Biomass-To-Liquid (BTL) processes for the manufacture of liquid hydrocarbon fuels. Six BTL systems are modelled and evaluated which are based on pressurised oxygen gasification of woody biomass, and specifically on circulating fluidised bed and entrained flow gasification systems. Three fuel synthesis technologies are considered: Fischer-Tropsch synthesis, methanol conversion followed by Methanol to Gasoline (MTG) and the Topsoe Integrated Gasoline (TIGAS) synthesis.